As potencialidades informacionais do cinema: uma análise fílmica de Fahrenheit 451 (1966) - Rodrigues, Daniel Alves (Brasil, 2023)
It presents the results of the study carried out on the use of films as useful informational potential to be disseminated as sources for viewers. It deals with a case study carried out with the feature film Fahrenheit 451 (1966) to reach the solution of the research problem. It is based on the premise that information is present in different environments and, depending on the purpose of its producers, can be useful as an informational source, whether in films, theater, music, libraries, archives and museums. It uses film analysis as a methodology, supported by content analysis for data collection and the Generative Path of Sense (PGS) for analysis of results, classifying the research as exploratory and descriptive. It aims to investigate the informational potential of cinema through the analysis of the film object of study, identifying and presenting the potential contained in it. Indicates as results 8 potentialities found, of which 6 are addressed by the film, namely: self-knowledge, culture, education, politics, social and technology. It is hoped that this investigation can serve as a reference for further research in the area of Librarianship, based on film analysis to find new potentialities within films, so that cinema can increasingly be seen as a potential informational source.